COMPARATIVE MIGRATORY PATTERN OF Ascaris suum, Toxocara vitulorum AND Toxocara canis IN A RABBITE MODEL - S. Pramanik (Director of Academics and Research, Kerala Veterinary and Animal Sciences University, 1995)
Comparative migration and distribution of A. suum, T. vitulorum and T canis larvae in the tissue of rabbits infected orally with 5x10° infective eggs for 63 DPI period were studied. Total larval yield at necropsy revealed 0.484- 6.658%, 0.12-4.364% and 5.24-17.46% recovery respectively from infected rabbits. Peak larval recovery was noticed on 7,3 .and 14 DPI respectively and liver was the prime orgain where maximum larvae inhabited. Among the three ascarids, only T canis larvae crossed the blood brain barrier and reached the brain in good numbers